The T-Cell Inhibitory Molecule Butyrophilin-Like 2 Is Up-regulated in Mild Plasmodium falciparum Infection and Is Protective During Experimental Cerebral Malaria. (15th April 2015) - Subramaniam, Krishanthi S.; Spaulding, Emily; Ivan, Emil; Mutimura, Eugene; Kim, Ryung S.; Liu, Xikui; Dong, Chen; Feintuch, Catherine M.; Zhang, Xingxing; Anastos, Kathryn; Lauvau, Gregoire; Daily, Johanna P.
Abstract: Plasmodium falciparum infection can result in severe disease that is associated with elevated inflammation and vital organ dysfunction; however, malaria-endemic residents gain protection from lethal outcomes and manifest only mild symptoms during infection. To characterize host responses associated with this more effective antimalarial response, we characterized whole-blood transcriptional profiles in Rwandan adults during a mild malaria episode and compared them with findings from a convalescence sample. We observed transcriptional up-regulation in many pathways, including type I interferon, interferon γ, complement activation, and nitric oxide during malaria infection, which provide benchmarks of mild disease physiology. Transcripts encoding negative regulators of T-cell activation, such as programmed death ligand 1 (PD-L1), programmed death 1 ligand 2 (PD-L2), and the butyrophilin family member butyrophilin-like 2 (BTNL2) were also increased. To support an important functional role for BTNL2 during malaria infection, we studied chimeric mice reconstituted with BTNL2 −/− or wild-type hematopoietic cells that were inoculated with Plasmodium berghei ANKA, a murine model of cerebral malaria. We found that BTNL2 −/− chimeric mice had a significant decrease in survival compared with wild-type counterparts. Collectively these data characterize the immune responses associated with mild malaria and uncover a novel role for BTNL2 in the host response to malaria.